An insider's view of sexual science since Kinsey - Reiss, Ira L. (Rowman and Littlefield, 2006)
Ira Reiss presents to those interested in the work of sexual science a view of this field. The text provides a personal account of the author's experiences in sexual science that helps the reader understand many of the major issues that confront those insexual science.